2023
DOI: 10.1186/s12998-023-00474-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cultural competency among Canadian chiropractors: a cross-sectional survey of Canadian Chiropractic Association members

Abstract: Background There is a paucity of research assessing cultural competency among Canadian chiropractors. Therefore, the aims of this study were to (1) measure cultural competency among Canadian chiropractors, (2) understand chiropractors’ perspectives of challenges and attitudes regarding the delivery of chiropractic services to equity-seeking communities, and (3) assess contextual factors associated with cultural competency. Methods We conducted a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This study focused on assessing levels of cultural humility in student osteopaths, but ndings indicated that experiences of discrimination were often associated with lack of awareness or negative attitudes among staff, suggesting that staff training is urgently required. Similar ndings were found in Bakaa et al (49) who surveyed cultural competence in a sample of 3,000 chiropractors and suggested that gaps between knowledge and self-reported behaviour required further research to clarify barriers and guide future training.…”
Section: Educating Staffsupporting
confidence: 85%
“…This study focused on assessing levels of cultural humility in student osteopaths, but ndings indicated that experiences of discrimination were often associated with lack of awareness or negative attitudes among staff, suggesting that staff training is urgently required. Similar ndings were found in Bakaa et al (49) who surveyed cultural competence in a sample of 3,000 chiropractors and suggested that gaps between knowledge and self-reported behaviour required further research to clarify barriers and guide future training.…”
Section: Educating Staffsupporting
confidence: 85%
“…Cassidy, J. David from the University of Toronto, researches the epidemiology and risk factors of NP [ 44 ]. Cote Pierre, from the University of Ontario Institute of Technology, investigates the prevalence of NP, the efficacy of manual interventions, and the relationship between NP, depression, and anxiety [ 34 , 45 , 46 ]. Disc degeneration's association with NP [ 47 ], as well as the prevalence of NP, whiplash injury, physical therapy, manual therapy, randomized controlled studies, and systematic reviews, are important keywords in this field.…”
Section: Discussionmentioning
confidence: 99%